Growth characteristics of Suaeda salsa under different soil salinity gradients in controlled experiments - Zhang, Fei; Chen, Yun; Yuan, Jie; Ma, Ligang; Liu, Changjiang (International Journal of Agricultural and Biological Engineering, 2021)
Xinjiang is the province with the largest saline-alkali land in China. The growth of halophytes will be stressed when their salt content reaches the threshold. In this study, the pot experiments were conducted and Suaeda salsa, a typical halophyte, was selected as the object to explore the relationship between growth characteristics and salt content under different soil salinity gradients. Salinity gradients were set according to the maximum soil salinity in the current years of Ebinur Lake Wetland National Nature Reserve (ELWNNR). They were classified using the following threshold values: ≤2 g/kg (Control Group), 10 g/kg, 20 g/kg, 30 g/kg, and 40 g/kg. The original spectrum, trilateral position and growth characteristics were used as indexes for analysis. With the increase of soil salt content, the red edge shift occurs first, followed by the blue edge shift. The position of yellow edge, green peak and blue edge were not sensitive with the change of soil salinity. This indicates that the red edge is the best indicator for evaluating plant growth. Compared with the Control Group, when the salt content is less than 10 g/kg, the growth status of plant seems not significantly affected. However, plant growth begins to be stressed when the salt content increases to 20 g/kg, which is a turning point for plant health. The increase of soil salt content can inhibit chlorophyll synthesis and plant growth. Plants begin to die when the salt content reaches the 40 g/kg. Therefore, 40 g/kg could be regarded as the critical point of salt content which inhibits plant growth. The study also shows that the relationship between plant-height change rate and soil salt content is the most significant, indicating that the plant-height change rate is significantly impacted by soil salt content. Keywords: Suaeda salsa, soil salt content, gradient, spectral, growth characteristics DOI: 10.25165/j.ijabe.20211405.5871 Citation: Zhang F, Chen Y, Yuan J, Ma L G, Liu C J. Growth characteristics of Suaeda salsa under different soil salinity gradients in controlled experiments. Int J Agric & Biol Eng, 2021; 14(5): 142–148.